(untitled) (Modern education and development, 2025)
Vocabulary teaching is an essential component of language learning, as a rich and varied vocabulary is crucial for effective communication. In order to help students acquire and retain new words, it is important for educators to employ effective word-learning strategies in their teaching. By incorporating these strategies into their lesson plans, teachers can help students develop the skills they need to expand their vocabulary and become more proficient in the language.Intentional vocabulary teaching is a deliberate approach aimed at providing students with the necessary knowledge, skills, and strategies to expand their vocabulary, enhance their language proficiency, and effectively communicate in various settings. Researchers have offered different definitions of intentional vocabulary learning, with some, like Hulstijn, describing it as a method where learners are aware of what they are learning and engage in tasks focused on specific target vocabulary[3;349]. This thesis underscores the importance of intentional vocabulary teaching and explores the effectiveness of various word-learning strategies in improving vocabulary acquisition among language learners.